2004
DOI: 10.1038/sj.onc.1207492
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple cell-type-specific elements regulate Myc protein stability

Abstract: Myc is a highly unstable transcription factor that is destroyed by ubiquitin (Ub)-mediated proteolysis. We have previously identified an amino-terminal 'degron' within Myc that signals its destruction; this degron spans the transcriptional activation domain of Myc, and includes two highly conserved regions called Myc boxes I and II. We now report the identification of a second element -the D-element -which is also required for Myc proteolysis. The centrally located D-element is distinct from the PEST domain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…In contrast to wild-type PML, overexpression of a RING-defective mutant, lacking two structural invariant cysteins was unable to reduce Myc levels ( Figure 6a). In line with earlier studies that identified Myc box domains 1 and 2 and a short region partially overlapping with Myc Box 3 as sites determining Myc degradation (Salghetti et al, 1999;Herbst et al, 2004) the sensitivity of protein levels to PML is gradually lost by N-terminal truncation of the Myc protein ( Figure 6b). Next, we tested whether PML would enhance ubiquitination of Myc.…”
Section: Pml Isoform-specific Binding and Destabilization Of Mycsupporting
confidence: 91%
“…In contrast to wild-type PML, overexpression of a RING-defective mutant, lacking two structural invariant cysteins was unable to reduce Myc levels ( Figure 6a). In line with earlier studies that identified Myc box domains 1 and 2 and a short region partially overlapping with Myc Box 3 as sites determining Myc degradation (Salghetti et al, 1999;Herbst et al, 2004) the sensitivity of protein levels to PML is gradually lost by N-terminal truncation of the Myc protein ( Figure 6b). Next, we tested whether PML would enhance ubiquitination of Myc.…”
Section: Pml Isoform-specific Binding and Destabilization Of Mycsupporting
confidence: 91%
“…38,39 Outside the degron, the MBIII domain has also been shown to regulate c-MYC stability. 40 The binding of c-MYC to DNA relies on the CT region comprising basic (b) helix-loophelix (HLH) and LZ domains (bHLH-LZ) through heterodimerization with the MAX protein. 41 We first generated mutant FLAGtagged c-MYC proteins in which each of these specific domains was deleted (MBI, MBII, MBIII or CT) or mutant proteins at key positions for c-MYC stability (T58A and S62A) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that a smaller deletion (25-AA) that contains the defined 15-AA TAD (Kojima et al, 1997) slightly reduced ubiquitination but did not significantly stabilize KLF5 protein (Figure 3). The overlap between TAD and degron sequence could be due to the common acidic activation domain (Herbst et al, 2004).…”
Section: Discussionmentioning
confidence: 99%